Depression, anxiety and stress with possible sources of stressors among undergraduate medical students in Malaysia - Al-Ani, Ali Sabri Radeef; Faisal, Ghasak Ghazi (Ministry of Health and Universiti Brunei Darussalem, 2016)
It is well known that medical students are subject ed to different levels of stressors during various stages of their study. Exposure to severe and prolonged stressors may cause serious emotional disturbances in the form of depression, anxiety and stress which may hinder students’ academic performance, quality of life, and also their physical health. Therefore, this study aimed to determine the prevalence and severity of depression, anxiety and stress symptoms and also to determine the possible sources of stressors and their relationship with these symptoms among medical undergraduate students throughout the different stages of their study. A cross sectional study was conducted among 501 students from the Faculty of Medicine, International Islamic University Malaysia. Depression Anxiety, Stress Scale (DASS-21) was used to assess the prevalence and severity of depression, anxiety and stress. The sources of stressors were identified by giving the students a list of the most possible source of stressors which were chosen depending on previous studies. The overall prevalence of depression, anxiety and stress was 39.7%, 65.8% and 37.1% respectively but it was found that 7.2%, 29.7% and 7.4% of medical students have clinically significant depression,anxiety and stress respectively. The emotional disturbances were significantly higher among female students. Younger students aged ≤21 years were experiencing significantly higher mean score of depression, anxiety and stress. Regarding the source of stressors, the top ten stressors decided by the students were mainly academic and personal factors. Emotional disturbances in the form of depression, anxiety and stress are existing in medical students which require early intervention. Academic and personal factors can be considered as sources of stressors that may precipitate for depression anxiety and stress.